Epigenetics in psychiatry - Peedicayil, Jacob; Grayson, Dennis R.; Avramopoulos, Dimitri (Academic Press, 2014)
Epigenetics in Psychiatry covers all major areas of psychiatry in which extensive epigenetic research has been performed, fully encompassing a diverse and maturing field, including drug addiction, bipolar disorder, epidemiology, cognitive disorders, and the uses of putative epigenetic-based psychotropic drugs. Uniquely, each chapter correlates epigenetics with relevant advances across genomics, transcriptomics, and proteomics. The book acts as a catalyst for further research in this potentially very important and useful area of psychiatry. The elucidation of basic principles o.